Tampilan Sapi Bali yang Diberi Hijauan dan Penambahan Suplemen (Silase dan Mineral) di Pulau Malan, Katingan - Harmini Harmini; M. A. Firmansyah (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2016)
Waste of rice straw is abundance available and not used as animal feed source. This study was aimed to compare the performance of Bali cattle fed by forage only and supplemented by straw silage and mineral. Total of 12 bali cattle was used. Given 30% straw silage and 4% mineral of total feed was represented by 7 Bali cattled. Amount of 5 Bali cattle was given 100% forage. Measurement of body length, chest circumference, height and daily weight gain were measured. The results showed that the length and height in the group given supplements were higher (P<0,05) compared to forage only. While the bust and PBBH were higher and significantly different (P<0,05). It was concludes that feeding forage and supplemented with silage and minerals can increase the chest circumference and PBBH in Bali cattle. Keywords: rice straw, silage, minerals, Bali cattle.